Management of small perforated corneal ulcers: Training model in mammalian eye to enhance surgical skills of residents. Issue 2 (March 2022) - Bafna, Rahul Kumar; Tripathi, Manasi; Asif, Mohamed Ibrahime; Agarwal, Rinky; Lata, Suman; Kumar, Sushil; Sharma, Namrata
Purpose: To demonstrate a training technique on the mammalian eye for optimum Cyanoacrylate Tissue adhesive application in cases of perforated corneal ulcers. Methods: A full-thickness defect simulating a perforation was created on the goat's eye cornea to teach the technique of cyanoacrylate glue application in cases of corneal perforations to novice surgeons. Results: This training model on the mammalian eye was tested by 10 residents at our centre. All the 10 candidates involved in our series were newly joined Cornea fellows with proficient skill in cataract surgeries and minor ophthalmic procedures such as suture removal, chalazion excision, pterygium removal and administration of an intravitreal injection. None of the candidates had prior experience of corneal surgeries. Each resident made an average of 4.4 attempts to seal the corneal defect, obtain a regular corneal surface and form the anterior chamber. Conclusion: This training model helps in mastering one of the skills of corneal surgeries.